Effective legal research - Knowles, John , 1959-; Thomas, Phillip A. (Legal skills series, 2009)
'Effective Legal Research' helps students develop confidence in legal research. The book demonstrates the processes of consulting the various sources, & shows how to use a legal library. It uses diagrams, flowcharts, illustrations from print sources, & screen shots from web sources to explain research procedures